Meta-Analysis: The Effect of Neuropatic Complications and Depression Commorbidity on the Quality of Life of Patients with Type 2 Diabetes - Rofana Aghniya; Bhisma Murti; Didik Gunawan Tamtomo (Masters Program in Public Health, 2020)
Background: Diabetes mellitus is a metabolic disease that results from insulin insufficiency and often causes complications. DM patients are prone to depression. Depression is one aspect that affects the quality of life. Measuring the quality of life in DM patients is done as a measure of the success of the intervention. This study aims to estimate the influence of neuro